Lexical Bundles in Academic Presentations Given by PhD level EAP Students: A Literature Review - Nausa, Ricardo A. (GIST – Education and Learning Research Journal, 2013)
Lexical bundles are multiword units that perform a variety of discourse functions and are a characteristic of academic discourse genres. Their use is considered a marker of linguistic proficiency and necessary for successful adaptation to academic communities. This literature review, which is part of a proposal for the analysis of lexical bundles use by Colombian PhD-level EAP students in their academic presentations, (a) explores the concept of lexical bundles in academic discourses and (b) presents potential areas for their study in the academic presentation genre. The review makes particular emphasis on the lack of studies on lexical bundles use in the academic presentation as a genre as well as the lack of studies on spoken genres in situations in which English is used as a foreign language by PhD-level EAP students, particularly, in the Colombian context.